Performance and Environmental Evaluation of Stabilized Base Material with Strontium Slag in Low-Volume Road in China - Teng Wang; Qiulin Tao; Zhaoxing Xie (Advances in Civil Engineering)
Strontium slag, a by-product of the strontium carbonate refining industry, has been produced at million tons per year in China. The use of strontium slag in the roads could reduce the demand of virgin materials and help solve the environmental problems caused by strontium slag. However, it is necessary to evaluate its environmental effect and the performance of the pavement with strontium slag before it could be used in roads. In this study, two test sections with strontium slag base layer were paved in low-volume roads in China to investigate its performance and environmental impact: (1) cement-treated base (CTB) section (5 cm asphalt surface over 20 cm CTB containing strontium slag) and (2) lime-treated base (LTB) section (3 cm asphalt surface over 20 cm LTB with strontium slag). The performance of the test sections was evaluated through laboratory and field experiments. The cost and environmental effect of strontium slag were investigated using production cost analysis and life-cycle assessment, respectively. Results of this study indicate that the CTB section exhibited a better performance compared to the LTB section, and the strontium slag decreased the material cost and the emissions during production.